If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-1)=4(10-2x)
We move all terms to the left:
2(3x-1)-(4(10-2x))=0
We add all the numbers together, and all the variables
2(3x-1)-(4(-2x+10))=0
We multiply parentheses
6x-(4(-2x+10))-2=0
We calculate terms in parentheses: -(4(-2x+10)), so:We get rid of parentheses
4(-2x+10)
We multiply parentheses
-8x+40
Back to the equation:
-(-8x+40)
6x+8x-40-2=0
We add all the numbers together, and all the variables
14x-42=0
We move all terms containing x to the left, all other terms to the right
14x=42
x=42/14
x=3
| -8(x-1)-6x=-4x-12 | | 5-3x=-2x-7 | | −2(2x−9)=−10 | | 10g(g+5)=2(g+9 | | -9+2r=1+9r-6r | | 23=3(2n-6)+3n | | 1x+5=9x+6 | | x+1=6x-35 | | 6=x/4−8 | | -11(-8x+1)-6(-4+11x)=10x+11x | | 5x+10+35=11x-3 | | -2+4x-12=40 | | 9y+37=-7(y-3) | | 40h=-24 | | 3x+0.5(x+3)+4=14 | | T=4+5t | | m4−3=9 | | (y)+7=16 | | 12x-15=6–3x | | -u+2=-10+2u | | 4(2x-5)=7(x-1) | | (2x+1)º+(x-10)º=90º | | -8c=4-7c | | 4a+2a+9=6a+4+5 | | m+12=53 | | 1x+5=9x=6 | | 8=3x-4x-4 | | 2(x-4=22 | | 5(4x-9)-8=5(x-3)+52 | | 29=t-(-17) | | -2z=6.8z | | (2n)/(n+3)=0 |